Characterization of uncontrolled, severe asthma patients with type 2 inflammation (T2): results from a physician survey across countries from Latin American, Eurasian Middle East regions and China. (4th May 2022) - Kosoy, Irina; Lew, Elisheva; Ledanois, Olivier; Derrickson, William
ABSTRACT: Objective: The 2019 GINA guidance incorporates the presence of T2 inflammation in severe asthma patients to determine eligibility for add-on biologic therapy, though little data exists to characterize this population. The objective of this manuscript is to conduct a descriptive analysis to characterize patients with severe asthma in emerging countries based on disease severity, patient exacerbation history, and T2 phenotype. Methods: A cross-sectional survey of physicians treating asthma patients ages 12 years and older was conducted in eight countries. Physicians characterized their severe asthma patients and reported data from their patients' medical charts. Medical chart data was selected from the physicians' six most recent asthma patients taking prescription medication. Results: A total of 550 physicians completed the survey and filled out 3, 300 patient record forms. A total of 876 patients have been characterized with uncontrolled severe asthma. Of the 420 patients with available EOS lab data, 40% are indicated with T2 inflammation (EOS ≥150/µL). Ninety-one percent of all patients with available IgE lab data ( n = 498) had IgE 30 − 1500 IU/mL indicating allergy-driven asthma. Finally, chronic OCS use (as reported by physicians) was reported in 11% of patients. Conclusion: This research revealed that 65% of patients had at least one of three T2 inflammation comorbidities assessed: allergic rhinitis, chronic rhinosinusitis with nasal polyps, and atopic dermatitis. Discrepancies were observed between patients' treatment regimens and GINA step reported, suggesting there may be room to improve understanding of asthma severity as defined per GINA guidelines as well as asthma control assessment in clinical practice.